2011
DOI: 10.3945/jn.111.144105
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Inducible Factor-2a Is Translationally Repressed in Response to Dietary Iron Deficiency in Sprague-Dawley Rats

Abstract: Iron regulatory proteins (IRP) regulate cellular iron metabolism by binding to iron-responsive elements (IRE) located in untranslated regions of mRNA-encoding proteins of iron metabolism. Recently, IRE have been identified in mRNA-encoding proteins with previously uncharacterized roles in iron metabolism, thus expanding the role of IRP beyond the regulation of cellular iron homeostasis. The mRNA for HIF 2-α contains an IRE and undergoes iron-dependent regulation in vitro, though the translational regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Transcription is regulated by NF-κB [5] and numerous epigenetic factors [6], including microRNAs miR-155 [7], miR-199a [8], miR-30c-2-3p and miR30a-3p [9]. Translation is up-regulated through the Akt and Erk pathways [10], and inhibited by iron regulatory proteins IRP1/2 [11,12] and small regulatory molecules [13], interacting with the iron regulatory element in 5'-UTR of HIF-2α mRNA. AMPK decreases HIF-α production [14], and also orchestrates cellular response to energy stress in a HIF-independent manner [15,16].…”
Section: Introductionmentioning
confidence: 98%
“…Transcription is regulated by NF-κB [5] and numerous epigenetic factors [6], including microRNAs miR-155 [7], miR-199a [8], miR-30c-2-3p and miR30a-3p [9]. Translation is up-regulated through the Akt and Erk pathways [10], and inhibited by iron regulatory proteins IRP1/2 [11,12] and small regulatory molecules [13], interacting with the iron regulatory element in 5'-UTR of HIF-2α mRNA. AMPK decreases HIF-α production [14], and also orchestrates cellular response to energy stress in a HIF-independent manner [15,16].…”
Section: Introductionmentioning
confidence: 98%
“…An in vivo study reported that iron deficiency in liver significantly increased activity of IRP1 and IRP2, and thereby decreased translation of HIF2a mRNA 108 . Two recent studies demonstrated the importance of IRPs in Hif2a regulation using knockout mice.…”
Section: Introductionmentioning
confidence: 99%
“…Iron deficiency may further increase this fraction, as suggested by dietary experiments in rats 34 and by the recently reported translational repression of HIF2a mRNA in rat livers. 35 This response would further reduce Epo expression and erythropoietic activity under iron-limiting conditions. Hypoxia or increased iron supply favor conversion of apo-to [4Fe-4S]-IRP1, which acts as cytosolic aconitase and fails to bind to HIF2a mRNA, allowing HIF2a synthesis.…”
Section: Irp1mentioning
confidence: 99%